COVD-04. CHARACTERISTICS OF SARS-COV-2 IN 64 CHILDREN WITH CNS TUMORS: A REPORT FROM THE SIOP/ST. JUDE CHILDREN'S RESEARCH HOSPITAL (SJCRH) GLOBAL COVID-19 CHILDHOOD CANCER REGISTRY. (4th December 2020) - Moreira, Daniel; Bouffet, Eric; Bhakta, Nickhill; Chantada, Guillermo; Chen, Yichen; Faughnan, Lane; Vedaraju, Yuvanesh; Avula, Maghana; Homsi, Maysam; Naidu, Paula; Pappas, Andrew; Ranadive, Radhikesh; et al.
Abstract: BACKGROUND: The GCCCR is a collaboration between SIOP and SJCRH to describe the natural history of SARS-CoV-2 in children with cancer across the world. METHODS: The GCCCR is a deidentified registry of patients <19 years of age with cancer or recipients of a hematopoietic stem cell transplant and laboratory-confirmed SARS-CoV-2 infection. Demographic data, cancer diagnosis, cancer-directed therapy, and clinical characteristics of SARS-CoV-2 infection were collected. Outcomes were collected at 30-days and 60-days post infection. RESULTS: As of August 10 th 2020, the GCCCR included 730 cases from 35 countries, including 64 children with CNS tumors (8.8%) from 17 countries. The most frequent diagnoses were embryonal tumors (31.2%) and low-grade glioma (17.2%). Thirty-nine (60.9%) children were asymptomatic from infection, while 19 (29.7%) patients required hospital admission and 2 (6.3%) transferred to the intensive care unit. There was a significant association between infection severity and ANC <500 (p=0.04). At the time of infection, 44 (68.8%) patients were undergoing cancer-directed therapy. Thirty-two cases have follow-up data. No modification in cancer-directed therapy occurred in 11 (34.4%) patients, while chemotherapy was modified in 6 (18.8%), radiotherapy delayed in 2 (6.3%), and surgery postponed in 1 (3.1%). No patients died from SARS-CoV-2 infection, although 2 died from non-COVID-19 related causes. CONCLUSION: The frequency and severity of COVID infection among children with CNS tumors appears to be proportionally lower compared to other children with cancer. Although this is the largest cohort of patients reported to date, additional insight is needed, including the effects of treatment modifications on outcomes.